Corrections to “Impact of longitudinal variation of the coupling coefficient due to bending and twisting on inter-core crosstalk in weakly-coupled MCFs” [Sep 18 3898-3911] - Cartaxo, A.; Tiago M. F. A. (Journal of Lightwave Technology, 2019)
The analysis presented in [1] considers the impact of the bending and twisting on the effective refractive index of the core in step-index weakly-coupled multicore fibers (MCFs). However, it has come to the attention of the authors that the analysis neglected its impact on the equivalent refractive indexes of the core and cladding. The effect of bending and twisting on the equivalent refractive indexes of the core and cladding, while without impact on the general expressions of the inter-core crosstalk (ICXT) power (expressions (27)-(29) in [1]), has a significant impact on the expressions of the slope of the logarithm of the inter-core coupling coefficient (ICCC) (expressions (36)-(66) in [1]), and on the level of induced mean ICXT power.